A Study Of Corellation Between Attitude Toward Company Program: Psyche and Employee Performance at PT Pertamina EP - Chrisna Nuraisyiah; Henndy Ginting (Trunojoyo University of Madura, 2023)
This research aimed to investigate the correlation between employees' attitudes toward the company program, Psyche, and their performance at PT Pertamina EP, oil and gas company in Indonesia. The study also explored the potential relationship between employees' attitudes toward Psyche Program and their perceived performance. The findings of the research indicated that there was no significant correlation between employees' attitudes toward the company program and their performance. This suggests that employees' attitudes toward the Psyche Program did not directly influence their actual job performance at PT Pertamina EP. However, a significant correlation was observed between employees' attitudes toward the Psyche Program and their perceived performance. The absence of a correlation between attitudes toward the company program and actual job performance implies that factors other than attitudes, such as skill set, experience, and job-related competencies, might play a more prominent role in determining employee performance. These findings highlight the importance of considering various factors when evaluating and enhancing employee performance. On the other hand, the significant correlation between attitudes toward the Psyche Program and perceived performance indicates that employees' positive attitudes toward the program were associated with their perception of performing well in their roles. This finding suggests that the Psyche Program may have a positive influence on employees' subjective evaluation of their performance, leading to increased job satisfaction and motivation.